Influence of interaction between surface-modified magnetic nanoparticles with infectious biofilm components in artificial channel digging and biofilm eradication by antibiotics in vitro and in vivo. Issue 8 (22nd February 2021) - Quan, Kecheng; Jiang, Guimei; Liu, Jian; Zhang, Zexin; Ren, Yijin; Busscher, Henk J.; van der Mei, Henny C.; Peterson, Brandon W.
Abstract : Artificial channels dug by non-interacting nanoparticles in infectious biofilms enhance antibiotic penetration and bacterial killing  in vitro  and  in vivo . Abstract : Magnetic targeting of antimicrobial-loaded magnetic nanoparticles to micrometer-sized infectious biofilms is challenging. Bacterial biofilms possess water channels that facilitate transport of nutrient and metabolic waste products, but are insufficient to allow deep penetration of antimicrobials and bacterial killing. Artificial channel digging in infectious biofilms involves magnetically propelling nanoparticles through a biofilm to dig additional channels to enhance antimicrobial penetration. This does not require precise targeting. However, it is not known whether interaction of magnetic nanoparticles with biofilm components impacts the efficacy of antibiotics after artificial channel digging. Here, we functionalized magnetic-iron-oxide-nanoparticles (MIONPs) with polydopamine (PDA) to modify their interaction with staphylococcal pathogens and extracellular-polymeric-substances (EPS) and relate the interaction with in vitro biofilm eradication by gentamicin after magnetic channel digging. PDA-modified MIONPs had less negative zeta potentials than unmodified MIONPs due to the presence of amino groups and accordingly more interaction with negatively charged staphylococcal cell surfaces than unmodified MIONPs. Neither unmodified nor PDA-modified MIONPs interacted with EPS. Concurrently, use of non-interacting unmodified MIONPs for artificial channel digging in in vitro grown staphylococcal biofilms enhanced the efficacy of gentamicin more than the use of interacting, PDA-modified MIONPs. In vivo experiments in mice using a sub-cutaneous infection model confirmed that non-interacting, unmodified MIONPs enhanced eradication by gentamicin of Staphylococcus aureus Xen36 biofilms about 10 fold. Combined with the high biocompatibility of magnetic nanoparticles, these results form an important step in understanding the mechanism of artificial channel digging in infectious biofilms for enhancing antibiotic efficacy in hard-to-treat infectious biofilms in patients.